Republic of Belarus : Fifth Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report ;, 2014)
This Informational Annex highlights a voluntary assessment of the National Bank of the Republic of Belarus (NBRB) completed in April 2004. It concluded that there were significant vulnerabilities in the safeguards framework, especially in the legal structure and independence, external and internal audit, and financial reporting. The assessment made specific recommendations to correct the identified shortcomings. An updated assessment of the NBRB, which was completed in May 2009 in connection with the Stand-By Arrangement approved on January 12, 2009, found little progress in addressing previously identified vulnerabilities. The assessment determined that risks have increased since the voluntary 2004 assessment and recommended several measures. Only some of the recommendations were implemented by the NBRB.